Prevalence of bone fractures among children and adolescents with attention-deficit/hyperactivity disorder: a systematic review and meta-analysis - Hoda Seens; Shirin Modarresi; Joy C MacDermid; David M Walton; Ruby Grewal (BMC, 2021)
Abstract Background Attention-deficit/hyperactivity disorder (ADHD) is a significant neurodevelopment disorder among children and adolescents, with 5 % prevalence. Bone fractures account for 25 % of accidents and injuries among all children and adolescents. Considering the characteristics of inattention, hyperactivity, and impulsivity in children with ADHD, it is critical to examine bone fractures among these children. The objective of our meta-analysis was to determine the prevalence of bone fractures among children and adolescents with ADHD. Methods We completed a systematic review and meta-analysis using an electronic search of the following databases: CINAHL, EMBASE, PsycINFO, PubMed, and Scopus. The search terms used were: "attention deficit hyperactivity disorder OR attention deficit disorder" and "bone fracture*." We included studies examining patients 18 years or younger who were diagnosed with ADHD and tracked (prospectively or retrospectively) for five or more years. Effect size (es), using a random effects model, was calculated. We registered the review protocol with PROSPERO (CRD42019119527). Results From 445 records retrieved, 31 full text articles were reviewed and 5 articles met inclusion criteria for meta-analysis. The summary es revealed the prevalence of bone fractures among children and adolescents with ADHD to be 4.83 % (95 % CI: 3.07-6.58 %). The location of bone fractures, using a subset of data, showed a distribution of 69.62 %, 22.85 %, and 7.53 % in the upper limbs, lower limbs, and other anatomical regions, respectively. Another subset of studies revealed a 2.55-fold increase in the prevalence of fractures among the children with ADHD compared to their counterparts. Conclusions Awareness of these findings is critical to physicians, parents, and policy makers to create safe environments and provide supports in order to optimize the health and safety of children and adolescents with ADHD.